Xanthogranulomatous Oophoritis Masquerading as Malignant Ovarian Tumor: A Case Report - Gupta, Surbhi; Agarwal , Saumya Kamal; Rizvi, Shahzeen (Gynecology Obstetrics & Reproductive Medicine, 2025)
Xanthogranulomatous inflammation of the genital tract is uncommon but usually involves the endometrium. A 19-year-old girl presented with an abdominopelvic lump with a history of fever, irregular menses, and loss of appetite. On examination, a cystic, irregular, mobile mass of around 22-24 weeks’ uterine size was felt. On investigation, CA-125 was 16 U/mL, CA19.9 was 2.43U/mL, AFP was 0, and Inhibin B was 319.92 pg/mL. The CT scan mimicked ovarian malignancy. She underwent an exploratory laparotomy for the same reason, but upon rupture, cheesy material appeared from the mass. A frozen section was sent with pus culture showed no growth, and the pus culture showed no growth. However, the final histopathology report suggested foamy macrophages, neutrophils, and CD68-positive histiocytes, indicative of xanthogranulomatous oophoritis. Such patients present with a long-standing history of pelvic inflammatory disease and symptoms such as anorexia, fever, and lower abdominal pain. The radiological findings mimic ovarian malignancy. A frozen section can be helpful to rule out malignancy. Xanthogranulomatous oophoritis is a rare entity that poses a diagnostic challenge.